Tobacco and its negative impact: a case report - P. M., Arumugam (International Journal Of Community Medicine And Public Health, 2023)
One of the most valuable possessions one may have is good health. Nowadays, it is acknowledged that oral health and general health go hand in hand. Oral health can be characterized as a level of wellness for the mouth and associated tissues that enable someone to eat, speak, and interact socially without experiencing any active illness, discomfort, or embarrassment and that adds to overall well-being. Because of their widespread occurrence and major social impact, oral illnesses might be categorized as a public health issue. One strategy for the management of complicated health disorders is multidisciplinary collaborative care, which includes care coordination among clinicians. This case presentation describes a collaborative effort between healthcare providers and a patient enrolled in a tobacco cessation clinic. This is a case of a smoker aged 57 years, who started reducing cigarettes and had quit smoking 6 months prior based on the health belief model but his improvement in quality of life was not significant.